Effects of Group Music Therapy Combined with Dolphin Sounds on Mild Depression in Older Adults - Suttharat, Somkiat; Patchim, Napatsorn; Kamsuwan, Narissara; Kaewmukda, Narissa; Liangseree, Nuttamon; Sriphuchon, Nuntana; Buengsai, Nareerat; Luangbun, Nujchanat; Boonsak, Buntita; Chumnuan, Papawadee; Maipranate, Piyatida; Pootad, Piyatida; et al. (Journal of Health Science and Alternative Medicine, 2024)
Introduction: Music therapy can help increase serotonin levels. Dolphin sounds produce ultrasonic frequencies, which stimulate the human brain to release endorphins; as a result, depression can be reduced. This music therapy program effectively reduces depression scores in older adults. Methods: The sample consisted of 24 older adults with depression, divided into an experimental group and a control group selected by purposive sampling. The experimental intervention involved music therapy program sessions conducted once a day, 30 minutes per session, for a duration of 5 weeks, resulting in an index of item-objective congruence of 0.85. The Thai Geriatric Depression Scale (TGDS) was used to assess depression scores. Descriptive statistics included percentages, means, and standard deviations, while inferential statistics entailed the Wilcoxon signed-rank test and the Mann-Whitney U test, with the determination of significance at a=0.05. Results: After receiving the music therapy program, the experimental group had a significantly lower mean depression score than before the experiment (p-value < 0.010) and significantly lower than the control group receiving regular care (p-value < 0.010). Conclusion: The present study indicates that 30 minutes for 5 weeks of music therapy program intervention once a day is effective in reducing depression in older adults.